Eliminating world poverty, making governance work for the poor : a white paper on international development / [written and produced by Catherine Masterman ... et al.]. - Masterman, Catherine; Great Britain. Department for International Development (London : TSO, 2006)
With special reference to developing countries.
"Presented to Parliament by the Secretary of State for International Development by command of Her Majesty."
"DFID, Department for International Development"--Cover.
Includes bibliographical references.
Includes statistics.
osa19/06/13
Loans
Keywords: Economic assistance, British -- Developing countries; Poverty -- Developing countries; Economic development -- International cooperation